RELIABILITY OF THE COMPONENT UNITS OF EXCESSIVE WEAR OF COAL PREPARATION EQUIPMENT - Margareta, Duduiala Gianina; Alexandru, Florea Vlad (International Multidisciplinary Scientific GeoConference SGEM, 2014)
The paper presents the results of the working behavior of vibrating screens type SCC III 2.6x5.25 for a period of 29 months. Based on data obtained regarding operating times between failures and times consumed with repair work, it could be an analysis of reliability for some subassemblies, which presented significant wear; for example: splits, couplings, springs, troughs, beams, steel flats, etc. Time intervals to determine the relative and cumulative frequency as well as mean time between failures, failures rate and reliability variation depending on the time of operation based on distribution exponential and Weibull were calculated. The distribution law adopted (exponential or Weibull) was validated under test Kolmogorov, for each subassemblies analyzed. It is determine that the reliability of using distribution exponential and Weibull for subassemblies vibrating screens type SCC III 2.6x5.25 has great theoretical importance but mostly practical creating a data base of reliability parameters useful in practice to establish the required spare parts, preventive maintenance planning including maintenance organization based on reliability.